Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For $x \neq 0$, $$ 1 + 2 \sum_{n=1}^N \cos n x = \frac{ \sin (N + 1/2) x }{\sin \frac{x}{2}} $$

share|cite|improve this question

marked as duplicate by Martin Sleziak, Sami Ben Romdhane, 5xum, heropup, Yiorgos S. Smyrlis Feb 21 '14 at 9:51

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

This can be reduced to a geometric series just noting that $\cos nx =\frac{e^{inx}+e^{-inx}}{2}$. – Jon Jul 27 '12 at 7:57
@Jon Thank you very much! – Bamily Jul 27 '12 at 8:01
@Amanda You should not change other people's questions in the way which changes the meaning. If you want to ask for solution of some question using some specific method, you can ask a new question. (However, in this case there already is an answer using complex numbers.) This has been also discussed on meta: Why was this edit approved?. – Martin Sleziak Feb 21 '14 at 7:40
If you have a look at… and the question linked there, you can find several similar question. (Maybe some of these questions should be closed as duplicates?) – Martin Sleziak Feb 21 '14 at 8:09
up vote 11 down vote accepted

Here is a well known trigonometric trick $$ 1+2\sum\limits_{n=1}^N\cos (nx)= 1+\frac{1}{\sin(x/2)}\sum\limits_{n=1}^N 2\cos (nx)\sin (x/2)=\\ 1+\frac{1}{\sin (x/2)}\sum\limits_{n=1}^N(\sin (nx+x/2)-\sin (nx-x/2))=\\ 1+\frac{1}{\sin (x/2)}(\sin (Nx+x/2)-\sin (x/2))=\\ 1+\frac{\sin (Nx+x/2)}{\sin (x/2)}-1= \frac{\sin (N+1/2)x}{\sin (x/2)} $$ And this is a complex analysis approach $$ 1+2\sum\limits_{n=1}^N\cos(nx)= e^{i0x}+\sum\limits_{n=1}^N(e^{inx}+e^{-inx})= $$ $$ \sum\limits_{n=-N}^N e^{inx}= \frac{e^{-iNx}(e^{i(2N+1)x}-1)}{e^{ix}-1}= \frac{e^{i(N+1)x}-e^{-iNx}}{e^{ix}-1}= $$ $$ \frac{e^{i(N+1/2)x}-e^{-i(N+1/2)x}}{e^{ix/2}-e^{-ix/2}}= \frac{2i\sin(N+1/2)x}{2i\sin(x/2)}= \frac{\sin(N+1/2)x}{\sin(x/2)} $$

share|cite|improve this answer
Thank you Norbert, and $\sum_{n=0}^N $ should be changed to $ \sum_{n=1}^N$ above. – Bamily Jul 27 '12 at 9:25
Interesting how you managed to write an answer, even if there was no question... :D – J. M. Jul 27 '12 at 15:16
@J.M. I read the thought – Norbert Jul 27 '12 at 15:23

Not the answer you're looking for? Browse other questions tagged or ask your own question.